2020
DOI: 10.3390/jcm9041001
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study Evaluating the Effects of 670 nm Photobiomodulation in Healthy Ageing and Age-Related Macular Degeneration

Abstract: Limited evidence suggests that the application of 670 nm of red light alters the course of aged decline. A previous report on 18 patients showed regression of drusen and improvement in visual functions in patients with intermediate age-related macular degeneration (AMD) by 12 months. We evaluated the functional and structural effects of applying 670 nm light to 31 patients with intermediate AMD and 11 people aged 55 years or above with normal retina. The study eyes were treated daily in the morning with a 670 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 23 publications
0
14
0
Order By: Relevance
“…For this reason, Grewal et al exposed 42 eyes (12 controls, 30 intermediate AMD) to a simple easily reproducible Light Emitting Diode based light source for 120 seconds daily for 12 months. 49 At the end of the study period, no significant anatomic or functional changes were reported.…”
Section: Discussionmentioning
confidence: 91%
“…For this reason, Grewal et al exposed 42 eyes (12 controls, 30 intermediate AMD) to a simple easily reproducible Light Emitting Diode based light source for 120 seconds daily for 12 months. 49 At the end of the study period, no significant anatomic or functional changes were reported.…”
Section: Discussionmentioning
confidence: 91%
“…The parameters of irradiation used have varied widely, with the variation in the energy density ranging from 0.1 to 25 J/cm 2 , the variation in the irradiance ranging between 8 and 200 mW/cm 2 , and an irradiation duration anywhere between 80 and 250 s ( Table 2 ). However, several studies have reported that PBM plays a negative role in the treatment of progressed AMD, especially accompanied by DME with good visual eyesight [ 32 , 33 , 34 ] ( Table 3 ). Therefore, the progressive stage of retinal diseases is another factor that should be considered when adopting PBM to achieve the best clinical effects.…”
Section: Parameters Of Light Irradiationmentioning
confidence: 99%
“…The Food and Drug Administration recently approved the use of photobiomodulation therapy, which showed an effect on age-related macular degeneration (AMD), for clinical studies (8,9) . Although most studies demonstrated the benefits of red light or NIR treatment on experimentally induced retinal damage, the treatment seems to have more activity in the early stages of the disease in clinical practice.…”
Section: Introductionmentioning
confidence: 99%